Guided Gradual Egg-Tolerance Induction in Hen's Egg Allergic Children Tolerating Baked Egg: A Prospective Randomized Trial - De Vlieger, Liselot; Nuyttens, Lisa; Matton, Charlotte; Diels, Marianne; Verelst, Sophie; Leus, Jasmine; Coppens, Katrien; Sauer, Kate; Dilissen, Ellen; Coorevits, Lieve; Matthys, Christophe; Schrijvers, Rik; et al. (Frontiers in Allergy, 2022)
Background: Over the last years studies have shown that the majority of egg allergic children tolerate baked egg (e.g. cake), and that consuming baked egg accelerates the resolution of egg allergy. However, prospective studies demonstrating a home-based gradual reintroduction of egg over time, after baked egg tolerance, are limited while this could positively impact the children’s quality of life and nutrition. Objective: To investigate the clinically most favorable duration of gradual egg-tolerance induction in baked egg tolerant children at home, with regard to complete raw egg tolerance. Methods: Baked egg tolerant children above 12 months of age were randomly assigned to a short- or long arm protocol. In the short arm, egg-tolerance induction was studied over 18 months compared to 30 months in the long arm. Children were guided through this protocol involving the step-wise introduction of increasingly allergenic forms of egg starting with baked egg offered as cake, followed by hard-boiled egg, omelet/waffle/pancake, soft-boiled egg and finally raw egg. We hereby designed this protocol based on the influence of thermal processing in the presence or absence of wheat on egg proteins, as investigated by ELISA, SDS-PAGE and immunoblotting. At inclusion, children either passed an in-hospital cake challenge or had ovomucoid sIgE ≤ 1.2 kUA/L, which was considered safe for introduction at home. Results: Of the 78 children in the intention-to-treat group, 39 were randomized to each arm. Fifty-eight children reached the raw egg tolerance endpoint, of which 80% in the short arm and 69% in the long arm. Within the short arm the median time to raw egg tolerance was 24 months (95% CI, 21-27 months) compared to 30 months (95% CI, 28-32 months) in the long arm (P=0.005). No grade IV reactions or cases of eosinophilic esophagitis were observed. The short arm was considered to be non-inferior to the long arm. Conclusion: Our gradual short arm protocol appears to be safe and allows clinicians to guide baked egg tolerant children towards raw egg tolerance at home.